INTERVIEW WITH DEVON WOODS - Woods, Devon; Colombo Gomes, Gysele da Silva; Barcelos, Ana Maria Ferreira (Universidade do Estado do Rio de Janeiro, 2021)
On May 27th, 2021, we met virtually with Devon Woods. We asked him about his studies on beliefs and the relationship between beliefs and emotions and identity. We approached the decision-making process and its relationship to BAK (Beliefs, Assumptions and Knowledge). We also, discussed its relevance to English teaching communities, particularly here in Brazil. Devon Woods has always demonstrated to be amazed by the unseen and often unnoticed processes of interpretation that are involved in both personal and pedagogical types of communication. In the 1970s, he engaged in studies of learners’ and teachers’ cognition – their beliefs, interpretations and actions – and the interactions between them in language classrooms. As a product of his 1992 doctoral dissertation, we find his remarkable book “Teacher Cognition in Language Teaching” (1996), several articles, and the focus of the work of a number of graduate students published in the Carleton Papers in Applied Language Studies. The results of this conversation are what we present here in the form of an interview.